JESUS AND THE COMMANDMENT NOT TO STEAL - Tarrech, Armand Piug i (Sacra scripta, 2008)
Unlike the other commandments that form the second table of the Decalogue, the commandment not to steal is not paid special attention by Jesus. Nevertheless, analysis of the earliest materials from the Jesus tradition, attributed to Jesus himself, shows that this commandment, as the fifth (“you shall not kill”), becomes radicalised: Jesus states that the Kingdom goes beyond the binominal “I do not steal, I do not kill” that characterises the law-abiding. However, not killing is the first of the six antitheses in Matt, but there is no antithesis dedicated to not stealing. Only in the fifth antithesis are there some logia that radicalise this precept. These logia, which are also to be found in Luke’s Sermon on the Plain, specify that the violence implied in robbery has to be turned into generosity. The most radical logion is the one in Luke 6,30. The healing of hostility felt against those who have taken one’s possessions is possible thanks to one’s detachment from those possessions. Thus, despite the fact that Matt does not directly typify this form of behaviour as an antithesis, generosity represents the radicalisation of the commandment not to steal. If one’s heart is full of generosity, then it does not want to steal nor, when robbed, want to respond with revenge. Jesus’ position with regard to this commandment has to be seen in a broader context: his assessment of riches and money as barriers to entry to the Kingdom. The decisive text is the logion that states the impossibility of having two masters (Matt 6,24 par). Generosity is possible because the heart, which is able to give up the riches of this world, focuses on the treasure of the Kingdom alone. In Jesus’ ethics, then, the commandment not to steal is easily kept to. The question is not about sharing out inheritances (Luke 12,13- 14) but about understanding Luke’s summary of Jesus’ position: “a man’s life does not consist in the abundance of his possessions” (Luke 12,15).